A review of the Chinese species of Bothropolys Wood, 1862 (Chilopoda: Lithobiomorpha: Lithobiidae) - Ma, Hui-Qin; Song, Da-Xiang; Zhu, Ming-Sheng (Zootaxa, 2008)
The present paper reviews the centipede species of the genus Bothropolys Wood, 1862 (Lithobiomorpha: Lithobiidae) of the Chinese fauna, including two species recorded from China for the first time. Diagnoses of the genus and the species, detailed account on species distribution and a key to the Chinese Bothropolys species are included.